3D hierarchical porous N-doped carbon quantum dots/vanadium nitride hybrid microflowers as a superior electrode material toward high-performance asymmetric capacitive deionization. Issue 7 (10th June 2021) - Zhao, Jingxuan; Zhao, Zhibo; Sun, Yang; Ma, Xiangdong; Ye, Meidan; Wen, Xiaoru
Abstract : 3D hierarchical porous NCQDs/VN hybrid microflowers were first demonstrated as an advanced electrode for an asymmetric capacitive deionization of saline water. Abstract : Considering the time-consuming preparation, processing and unsatisfactory desalination capacity of carbon nanomaterials, the exploration of efficient electrode materials for practical capacitive deionization (CDI) applications has gained importance yet remains a great challenge. In this paper, porous N-doped carbon quantum dots/vanadium nitride (NCQDs/VN) microflowers were prepared via a facile one-step hydrothermal method accompanied by nitrogenization using NH3 and are proposed as an advanced electrode for CDI. The hybrid microflowers assembled by well-connected nanosheets provide highly open frameworks and a hierarchically porous alignment ( e.g., mesopores and macropores). Because of the specific microstructures and enhanced electrochemical conductivity arising from the synergistic effect of metallic VN and conductive NCQDs, the hybrid electrode displayed enhanced electrochemical performance and CDI behavior. The calculated GACNaCl value of NCQDs/VN reached 23.71 mg g −1 in a 500 mg L −1 NaCl solution under an external voltage of 1.4 V. Moreover, the porous NCQDs/VN-based asymmetric CDI cell demonstrated excellent durability. The desalination capacity retention was about 100% over 50 cycles, and the coulombic efficiency was relatively stable at about 90% of the initial value even after 10 000 continuous GC cycles. These impressive results validate that the NCQDs/VN hybrid microflowers have great potential for high-performance ( e.g., high capacity and good stability) CDI.